Academic Capacity Building of Lecturers through International Collaboration:: Empowerment Program with Universities in Malaysia - Yunus, Asraf; Hakim, Abdul; Nur, Muh (Institute of Education and Social Research, 2024)
This international community service program aims to enhance the academic capacity of lecturers through collaboration with universities in Malaysia. The program is designed to address the issue of lecturer quality by leveraging the exchange of knowledge and innovative teaching methods. The implementation method includes establishing a baseline, analyzing needs, conducting workshops, evaluating results, developing sustainable solutions, and the role of contributions from related parties. This article highlights the importance of international collaboration in higher education and its contribution to the development of lecturer capacity and the improvement of educational quality. Through this program, an increase in lecturer competence is expected, which in turn can strengthen the bilateral relations between Indonesia and Malaysia in the higher education sector learning.